POST ELECTION REPORT TAN/C.A.R.E. - NO ON PROP 10 CAMPAIGN - HULSE,B (Tufts Archival Research Center, 2007)
Post election report on proposition 10 in california which would require separate spaces for smokers and non smokers. Credits much of the defeat with th activities of California TAN volunteers. Provides an outline of the TAN strategy to defeat the proposition.